The Relationship Between Vitamin D Levels and Cardiac Remodelling in a Pediatric Dilated Cardiomyopathy Population: A Case-Control Study - Asmaa Carla Hagau; Ioana-Octavia Matacuta-Bogdan; Lacramioara Eliza Chiperi; Beatrix-Jullia Hack; Iolanda Muntean (Journal of Cardiovascular Development and Disease)
Dilated cardiomyopathy (DCM) is a significant contributor to heart failure (HF) in the pediatric population despite its lower incidence compared to adults. Method: We present a case-control study that investigates serum levels of Vitamin D, measured as 25-hydroxyvitamin D (25-OHD), in children diagnosed with DCM and explores the relationship between Vitamin D levels and left ventricular (LV) dimensions and systolic function. Results: Thirty patients (mean age: 10.61 ± 6.54 years) with DCM were included, with a control group of thirty-one matched healthy children. We found a high prevalence of 25-OHD deficiency (67%) in the DCM group, which was statistically significant compared to the control group (p < 0.05). Notably, a significant negative correlation was observed between 25-OHD levels and both LV end-diastolic diameter (LVEDD; r = −0.43, p < 0.01) and end-systolic diameter (LVESD; r = −0.46, p < 0.01). However, no significant correlation was found between Vitamin D levels and LV ejection fraction or shortening fraction. Conclusion: These findings emphasise the importance of assessing Vitamin D status in pediatric DCM patients and may suggest that Vitamin D supplementation can be beneficial in managing this condition through its potential effects on cardiac remodelling and function. Further research is warranted to clarify the underlying mechanisms and therapeutic implications.